Protective Effects of Aqueous Extract of Piper nigrum Whole Fruits Against Tramadol-induced Hepato-and Nephrotoxicity in Wistar Rats - Nurudeen, Quadri; Abdullahi, Sulyman; Falana, Mansurat Bolanle; Asinmi, Muhammed Robiu; Dikwa, Muhammad Ali; Oweh, Oghebetega ThankGod (Journal of Science and Technology, 2024)
Tramadol, a widely used analgesic, is becoming more abused in most countries. Hence, this study aims to investigate the protective effects of aqueous extract of Piper nigrum whole fruits on tramadol-induced toxicity in male Wistar rats. Six groups (A-F) of male Wistar rats were exposed to a 14-day oral treatment. Specifically, the control group, induced group (tramadol at 60 mg/kg), reference drug group (Vitamin C at 250 mg/kg) and the extract groups (250, 500, and 1000 mg/kg). The levels of liver cellular markers ALT, AST and ALP as well as the kidney function parameters (urea, creatinine and uric acid) showed a significant (p<0.05) increase following the administration of 60 mg/kg of tramadol and a significant reversal was observed following the administration of extract in a dose dependent manner. However, K+ and HCO3- showed a significant (p< 0.05) decrease and were also reversed following the administration of extract in a dose dependent manner. Tramadol also showed a significant (p<0.05) increase in the concentration of WBC and LYM, and a significant (p< 0.05) decrease in the levels of RBC, HGB, HCT, RDW-SD, RDW-CV, and MPV. The reference drug and the extract showed significant (p< 0.05) reversal in the levels of these biochemical parameters. Histological examination revealed normal liver and kidney architecture in all groups, indicating no signs of inflammation or damage. These findings revealed that the aqueous extracts from whole fruits of P. nigrum at concentrations of 250 and 500 and 1000 mg/kg may potentially offer protection and general improvement in the overall health status and function of the hematopoietic system.